Pengaruh Kredibilitas Karin Novilda sebagai Celebrity Influencer Produk Liquid Vape “CANDU terhadap Minat Beli Followers Instagram - Alam, Mutiara Nur; Yuliasari, Ika (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Since the last few years, many business people have started to switch their market into digital and use technology to promote their products. They started to use social media influencers as a part of promotion. An influencer can be seen for their credibility from how high their followers buy interest. Karin Novilda is a celebrity endorser on Instagram or commonly known as Awkarin. Currently, the number of Awkarin's followers is 7.9 million people. With the large number of her followers and current popularity, this is certainly considered very possible to influence her followers' buying interest in the